Desindustrialização, especialização produtiva e macrologística: considerações para o caso brasileiro - Borba, Romênia Virgínia Pimentel (2015)
This study aimed to investigate if Brazil is going through a processo of deindustrialization and the role of logistics infraestructure in this process. The importance of this application is centred on the fact that the industry is the most dynamic activity of the economy and because of the logistics infraestructure investment is frequently appointed on a recurring basis as critical to the competitiveness of international trade. Joint assessment of these indicators comfirm the hypothesis that in Brazil is a deindustrialization process. For the realization of logistical study were collected secondary data from federal projects in logistics infraestruture provided in Growth Accelation Program (PAC) and the Logistics and Transportations Nacional Plan (PNLT). The results showed that the increases in infraestructure not reversed the deindustrialization process in progress. In fact, they contributed to the consolidation of an essentially primary export base